The salinity front of the Río de la Plata - A numerical case study for winter and summer conditions - Simionato, Claudia Gloria (2001)
A 3-D baroclinic model has been applied to investigate the location of the salinity front of the Río de la Plata. River run-off, tides and mean winds for summer and winter conditions respectively were considered in order to find out the most important factors for the observed seasonal variability of this location. The results show that wind forcing is responsible for the observed variability in summer. In winter, wind forcing is not important, but the river discharge. The resulting surface salinity distributions show a surprisingly good agreement with the present knowledge from observations.